Awal Masuk dan Perkembangan Perkebunan Karet di Lampung Pasca Orde Baru - Jovanda, Renaldy; Meta Iskarina; Tata Atmadewi (Universitas Veteran Bangun Nusantara, 2024)
The objectives of this study are 1) to determine the beginning of entry of rubber plantations in Lampung, 2) to determine the condition of rubber plantations in Lampung after the New Order, 3) the determine the sosio-economic conditions of rubber farmers in Lampung after the New Order. The method used in this research is the historical method which includesh heuristics,ccriticism/ verification,i interpretation, and historiography. The resultssand this study state that at the beginning of the 20th century rubber began to be developed in Lampung Initially rubber was planted in the Bogor BotanicallGardens as a collection which was then introduced in 1864 in Indonesia Lampung is one of the largest rubber-producing areas in Indonesia considering that the area has climate, soil type and land area suitable for rubber plantations. This sector is expected to become a driving force for the municipal economy and the main sourceeof income for the people of Lampung Province.